ANALISIS SOAL MATEMATIKA TIPE HIGHER ORDER THINKING SKILLS (HOTS) TINGKAT SMP - Oktafiana, Lelly; Iis Holisin; Himmatul Mursyidah (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2019)
This study aims to describe the quality of the 2018 Mathematics National Examination (UN) in the HOTS types at the junior high level in terms of the level of validity, reliability, problem differentiation power, level of difficulty and distractor. This type of research is a descriptive study. The research was conducted at SMP Muhammadiyah 4 Surabaya and SMP Negeri 13 Surabaya for students in class VIII. The data collection technique used is a test. The test was taken from the 2018 math UN questions in odd semester VIII grade material including HOTS type. The number of UN mathematics questions in 2018 in the odd semester VIII class material consisted of 12 questions with 25% including LOTS types and 75% including HOTS types. The results showed: (1) 100% valid test questions, (2) high question reliability, (3) good problem differentiation power, (4) the difficuly level of the question 77,77% categorized as moderate and 2 question 22,23% are categorized as difficult, (5) there are 2 questions with one of the answer options do not work.